2018
DOI: 10.1590/s2175-97902018000400228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wet mass on dextromethorphan hydrobromide matrix pellets

Abstract: Dextromethorphan hydrobromide (DM) sustained release matrix pellets containing 10% w/w drug were prepared by an extrusion/spheronization technique. The effect of mixing different concentrations of ethyl cellulose (EC), hydroxypropyl methylcellulpse (HPMC K10), and Carbopol 934 with Avicel PH101 on the rheological properties of pellet wet mass was evaluated using mixer torque rheometry (MTR). The prepared pellets were characterized for size, drug content, and in-vitro DM release rate. The results showed that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(24 reference statements)
2
3
0
Order By: Relevance
“…3. Consequently, a typical torque profile that has been reported in previous studies on other powders (for instance, pharmaceutical powder 11,20,23,33,34) ) was obtained even in the case of iron ore powders.…”
Section: Torque Profile As a Function Of Water Contentsupporting
confidence: 66%
See 1 more Smart Citation
“…3. Consequently, a typical torque profile that has been reported in previous studies on other powders (for instance, pharmaceutical powder 11,20,23,33,34) ) was obtained even in the case of iron ore powders.…”
Section: Torque Profile As a Function Of Water Contentsupporting
confidence: 66%
“…The measurement of the agitation torque of wet powder has been employed for pharmaceutical powders. 13,[23][24][25] It has been demonstrated that the optimum water content for wet granulation of pharmaceutical powders can be determined based on their PL value. 13,23,25) However, there has been no attempt to utilize the agitation torque of ore powders to determine the optimum water content for wet granulation of iron ore powders.…”
Section: Determining Optimum Water Content For Iron Ore Granulation U...mentioning
confidence: 99%
“…A low pellet wet mass consistency enables easy extrusion of pellets and yields small pellets with smoother surfaces. A similar finding was obtained by Ibrahim and Mahrous [22].…”
Section: Effect On Pellet Sizesupporting
confidence: 91%
“…The required volume of the PVP solution was added, and the powder was wetted with the binder solution for 10 min. The obtained wet mass was then subjected to extrusion through a screen pore size of 1 mm Ø (Mini Screw Extruder, Model MSE1014; Caleva, Dorset, UK) at an extrusion speed of 100 rpm [22]. Consequently, the produced rod-shaped extrudates were spheronized for 5-7 min at a speed of 700 rpm using a rotating plate of even cross-hatch geometry (Spheronizer Model 120; Caleva, Dorset, UK).…”
Section: Extrusion/spheronization Proceduresmentioning
confidence: 99%
“…However, these methods are empirical and trial-and-error. As a comprehensive method to determine the optimum water content, the effectiveness of agitation torque measurement has been reported 10,[20][21][22] ; however, these studies focused on the wet granulation process of organic powders such as pharmaceutical materials 10,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%